Two new species of clearwing moths (Lepidoptera: Sesiidae) from Taiwan - Liang, Jia-Yuan; Hsu, Yu-Feng (Zootaxa, 2017)
Two new species of Sesiidae (clearwing moth) are described from Taiwan: Ceratocorema woodstocki Liang & Hsu sp. nov., and Melittia tao Liang & Hsu sp. nov. Diagnostic characters for the two species are presented using wing morphology, wing pattern, presence of androconial patches on the hindwing, and genitalia. The adults and their genitalia are documented, and distribution data are provided. New records of relationships between host plants and the immatures are also provided.